Total glucosides of peony ameliorates Sjögren's syndrome by affecting Th1/Th2 cytokine balance - WU, GUOLIN (Exp Ther Med, 2016)
The present study aimed to investigate the molecular mechanisms underlying the effects of total glucosides of peony (TGP) in the treatment of Sjögren's syndrome (SS). A total of 40 mice with SS were evenly assigned into four groups, including: Control group; TGP group, receiving 1 mg TGP daily; hydroxychloroquine (HCQ) group, receiving 0.25 mg HCQ daily; and a combined group, receiving 1 mg TGP and 0.25 mg HCQ daily. After 8 weeks, quantitative polymerase chain reaction and an enzyme-linked immunosorbent assay were used to detect the levels of interferon-γ (IFN-γ), interleukin-4 (IL-4), Fas and FasL in each group of mice. In addition, immunohistochemical analysis was used to determine the expression levels of IFN-γ and IL-4. IFN-γ, IL-4, Fas and FasL levels were significantly increased in the control group compared with the other three groups (P<0.05). Furthermore, the expression levels of these factors were reduced in the combined group in comparison with the HCQ group (P<0.05). The ratios of IFN-γ to IL-4 were decreased in the TGP and combined groups compared with the control group (P<0.05). The present results indicate that TGP ameliorates SS by affecting the Th1/Th2 cytokine balance and decreasing the expression levels of IFN-γ, IL-4, Fas and FasL. Therefore, TGP may represent a potential novel therapeutic agent for the treatment of SS.